Currículo escolar: possibilidade de apoio ao enfrentamento da violência doméstica (estudo de uma prática em São José dos Campos/SP) - Ando, Daniela de Araújo (2011)
This study aims at researching educational actions developed within the facilities of an Elementary School, in São José dos Campos/São Paulo, which may provide subsidies to build up a school curriculum that implies the possibility to fight against domestic violence. This study has been developed on qualitative approach grounds, using literature, document analysis, participating observation, field journal and interviews with 13 educators. The study evidenced a set of actions which is in constant development and renewal within the school being researched that unfolds the possibility of the school curriculum to give support to the fight against domestic violence. The challenges to create a school curriculum that implies fighting domestic violence against children are huge, but this is a path to be opened by the school as an institution, starting from a critical look at its reality, aiming at elaborating a curriculum attached to the actual concerns of students, educators, and community. It is expected that, with this study, the society can be offered proposals to fight domestic violence against children, having a democratic school curriculum as the baseline, involving, thus, students, educators and the community in the prevention and fight against domestic violence